1999
DOI: 10.1007/s004380051052
|View full text |Cite
|
Sign up to set email alerts
|

The eff-482 locus of Sinorhizobium meliloti CXM1-105 that influences symbiotic effectiveness consists of three genes encoding an endoglycanase, a transcriptional regulator and an adenylate cyclase

Abstract: The mutant T482 of Sinorhizobium meliloti CXM1-105, which carries a Tn5 insertion on megaplasmid 1, exhibits an enhanced symbiotic efficiency phenotype. Three genes, eglC, cya3 and syrB2, were identified in the eff-482 region tagged by the Tn5 insertion in T482. The eglC gene encodes an endoglycanase which contributes to the depolymerization of the exo-polysaccharide succinoglycan. The N-terminal region of the predicted cya3 gene product was similar to eukaryotic-type adenylate cyclases from Brevibacterium liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 76 publications
0
22
0
5
Order By: Relevance
“…The present study is the first to suggest a role for quorum sensing in the production of LMW succinoglycan. The endoglycanases ExsH and EglC, both of which play a role in the synthesis of the LMW fraction of succinoglycan required for the successful invasion of the plant host (49,66), seem to be controlled by quorum sensing. We have confirmed that indeed, the exsH gene is expressed at a higher level in the presence of the ExpR regulator and an active Sin system (see Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study is the first to suggest a role for quorum sensing in the production of LMW succinoglycan. The endoglycanases ExsH and EglC, both of which play a role in the synthesis of the LMW fraction of succinoglycan required for the successful invasion of the plant host (49,66), seem to be controlled by quorum sensing. We have confirmed that indeed, the exsH gene is expressed at a higher level in the presence of the ExpR regulator and an active Sin system (see Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Image acquisition and data analysis were performed as described previously (4,49). In brief, mean signal and mean local background intensities were obtained for each spot of the microarray images by using the ImaGene 5.0 software for spot detection, image segmentation, and signal quantification (Biodiscovery, Inc., Los Angeles, Calif.).…”
Section: Methodsmentioning
confidence: 99%
“…13), a functional copy of the groESL chaperonin operon (14), and genes needed for catabolism of betaines (15). However, except for syrB and a locus that inf luences symbiotic effectiveness (16), little was known outside this 275-kb region. Recently, an alcohol dehydrogenase (adhA; ref.…”
mentioning
confidence: 99%
“…Выявление генов обеих групп представляет большой интерес для конструирования хозяйственноценных штаммов ризобий, которое может быть связано как с усилением активности генов первой категории, так и с элиминацией генов второй категории. Генетичес-кие модификации обоих типов описаны в литературе (Bosworth et al, 1992;Sharypova et al, 1998), одна-ко, как показала наша работа, они смогут обеспечить существенное возрастание эффективности симбиоза только в сочетании с оптимизацией общей структуры микробно-растительной системы, обеспечивающей высокие частоты N 2 -фиксирующих штаммов в клу-беньках растений.…”
Section: специфичность симбиозаunclassified